2013
DOI: 10.1136/gutjnl-2013-305962
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblastic cells function as progenitors to regenerate murine livers after partial hepatectomy

Abstract: Objective Smoothened (SMO), a co-receptor of the Hedgehog (Hh) pathway, promotes fibrogenic repair of chronic liver injury. We investigated the roles of SMO+ myofibroblasts (MF) in liver regeneration by conditional deletion of SMO in αSMA+ cells after partial hepatectomy (PH). Design αSMA-Cre-ERT2×SMO/flox mice were treated with vehicle (Veh) or tamoxifen (TMX), and sacrificed 24 to 96 hrs post-PH. Regenerating livers were analyzed for proliferation, progenitors, and fibrosis by qRT-PCR and quantitative-IHC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 57 publications
8
99
0
Order By: Relevance
“…Future research should address whether MSC populations are connected to stem cell niches within the canals of Hering and contribute to progenitor cell formation. Monitoring of hepatic differentiation of MSC populations and mesodermal proteins in epithelial cells in ductular reactions, as demonstrated in this study, as well as recent lineage-tracing experiments with the Acta2 promoter (18,19), support this possibility.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Future research should address whether MSC populations are connected to stem cell niches within the canals of Hering and contribute to progenitor cell formation. Monitoring of hepatic differentiation of MSC populations and mesodermal proteins in epithelial cells in ductular reactions, as demonstrated in this study, as well as recent lineage-tracing experiments with the Acta2 promoter (18,19), support this possibility.…”
Section: Discussionsupporting
confidence: 54%
“…Quiescent stellate cells are typically located between sinusoidal endothelial cells and hepatocytes in the space of Disse, which has characteristics of stem cell niches (14,15). Moreover, activated stellate cells can develop into hepatocyte-like cells in vitro (14,16), and fate-mapping experiments using Gfap and Acta2 promoters indicate that they contribute to liver regeneration in vivo (17)(18)(19). In contrast to this, lineage-tracing experiments with lecithin retinol acyltransferase (LRAT) and mesoderm posterior 1 homolog (MESP1) failed to demonstrate a differentiation of HSCs into epithelial cells during regeneration of the injured mouse liver (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the possibility exists that Hh regulates SPP1 expression in tubules both via GLI1 and SOX9 pathways. Furthermore, Hh signal may directly influence myofibroblastic transformation of HSCs [37,38], and excessive SOX9 expression in fetal hepatocytes may mediate ectopic extracellular matrix deposition characteristic of fibrosis by way of HSC transformation [39]. Thus, there appear to be multiple tubule-associated signal pathways in GALD that could contribute to fibrosis associated with expanded numbers of parenchymal tubules: Hh-driven SPP1 production, SOX9-driven SPP1 production, Hh-driven myofibroblastic transformation of HSCs, and SOX9-driven ectopic extracellular matrix deposition via HSC transformation.…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicated the potential of stellate cells to contribute to liver regeneration. Indeed, cell lineage-tracing and transplantation studies confirmed that stellate cells can differentiate into epithelial liver cells such as hepatocytes and bile duct cells also in vivo [31,32,33,34,35]. …”
Section: Hepatic Stellate Cells As Liver Resident Mesenchymal Stem Cellsmentioning
confidence: 99%